Respuestas
Respuesta dada por:
0
1/1 - 2/3 - 1/6 = x
6 - 4 -1 = 6x
1 = 6x
x = 1/6;
Respuesta: 1/6
6 - 4 -1 = 6x
1 = 6x
x = 1/6;
Respuesta: 1/6
Anónimo:
Explica mejor
Respuesta dada por:
0
Buenas
![denominadores: denominadores:](https://tex.z-dn.net/?f=denominadores%3A)
1 3 6I 2
1 3 3I 3
1 1 1
![Mcm= 6 Mcm= 6](https://tex.z-dn.net/?f=Mcm%3D+6)
![Efectuamos: Efectuamos:](https://tex.z-dn.net/?f=Efectuamos%3A)
![\frac{1}{1} - \frac{2}{3} - \frac{1}{6} = \frac{6-4-1}{6} = mas \frac {1}{6} \frac{1}{1} - \frac{2}{3} - \frac{1}{6} = \frac{6-4-1}{6} = mas \frac {1}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B1%7D+-++%5Cfrac%7B2%7D%7B3%7D+-++%5Cfrac%7B1%7D%7B6%7D+%3D+++%5Cfrac%7B6-4-1%7D%7B6%7D+%3D+mas++%5Cfrac+%7B1%7D%7B6%7D+++)
Ley de signo:
menos (-) menos (-) = más (+)
![Respuesta: Respuesta:](https://tex.z-dn.net/?f=Respuesta%3A)
mas![\frac {1}{6} \frac {1}{6}](https://tex.z-dn.net/?f=+%5Cfrac+%7B1%7D%7B6%7D+)
1 3 6I 2
1 3 3I 3
1 1 1
Ley de signo:
menos (-) menos (-) = más (+)
mas
Preguntas similares
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años